ANALYSIS OF THE VALUATION AND DISPOSAL OF OPERATIONAL GOVERNMENT VEHICLES USING A MARKET VALUE APPROACH: Case Study of the Regional Goods Storage Center [BPAD] of DKI Jakarta Province - Marisi Sondang Tua; M.F Christiningrum (ESENSI: Jurnal Manajemen Bisnis, 2024)
This study aims to find out how the accounting recording method for the management of fixed assets of operational official vehicles at the Pusat Penyimpanan Barang Daerah BPAD Provinsi DKI Jakarta and to find out how to assess and write off vehicles that have expired their economic life by introducing a Market Data Approach. This study was conducted on Official Vehicles owned by Pusat Penyimpanan Barang Daerah BPAD Provinsi DKI Jakarta with a focus on calculating the fair value assessment of official vehicles that have expired their useful life (economic life). The research method used in this study is Descriptive Analysis, and the object of the study is official vehicles recorded on the Goods Inventory Card (KIB) according to the 2023 Audited Balance Sheet Report of Pusat Penyimpanan Barang Daerah BPAD Provinsi DKI Jakarta. The results of the study show that by following the rules/rules/guidelines on assessment, the Author can conduct an independent assessment of official vehicles as an alternative to using private appraisal/appraisal services. Improving employee competence and forming a team of Regional Property appraisers is deemed necessary for cost effectiveness and efficiency.